Plasma reforming of ethanol in DGCLW discharge - Yukhymenko, V.V.; Chernyak, V.Ya.; Olszewski, S.V.; Sidoruk, S.M.; Demchina, V.P.; Levko, D.S.; Shchedrin, A.I. (Вопросы атомной науки и техники, 2011)
This paper presents the results of experimental and theoretical investigations of the process of non-thermal plasmaassisted reforming of aqueous ethanol solutions in the dynamic plasma liquid systems using the DC electric discharges in a gas channel with liquid wall. The experiments show possibilities and efficiency of low-temperature plasmachemical conversion of liquid ethanol into hydrogen-rich synthesis gas in different regimes. The numerical modelling clarifies the nature and explains the kinetic mechanisms of non-equilibrium plasma-chemical transformations in the plasma-liquid systems in different modes.